Analisis Pengaruh Respon Emosional dan Sistem Absensi Berbasis Wajah Terhadap Kedisiplinan Karyawan PT. SHA Solo - Osfaldio Juflayn Leonard Triyanto; Asnawi Hidayat (Pusat Riset dan Inovasi Nasional, 2026)
Work discipline is highly important as it influences how well and effectively employees perform their duties. The purpose of this study is to examine how employees’ emotional responses and a facial recognition based attendance system affect their work discipline at PT. SHA Solo. In recent years, the company has implemented a facial recognition based attendance system to improve transparency and reduce fraud such as proxy attendance. However, its implementation has also generated various emotional reactions among employees, which may influence their level of discipline. This study employed a descriptive quantitative method and collected data through a survey of 58 employees of PT. SHA Solo using questionnaires. The data were analyzed using multiple linear regression with SPSS version 25. The statistical test results indicate that emotional responses (X₁) and the facial recognition based attendance system (X₂) have a significant positive effect on employee discipline (Y), both partially and simultaneously. The coefficient of determination (R²) was 0.705, meaning that 70.5% of the variation in employee discipline can be explained by these two factors, while the remaining 29.5% is influenced by other variables not examined in this study. These findings suggest that maintaining employees’ emotional well-being and implementing an appropriate digital attendance system are complementary strategies for improving work discipline. This research contributes to the field of human resource management and provides valuable insights for companies implementing digital monitoring systems to promote fairness, accountability, and improved performance.